Implementation Of Computer-based Audit Techniques As Auditor Support In Detecting Financial Report Fraud - Merdekawati, Eka; Saleh, Rahmat; Pratiwi, Ratih (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
This study aims to analyze the influence of audit experience and professional skepticism on auditors' ability to detect financial statement fraud, with the application of Computer-Assisted Audit Techniques (CAATs) as a moderating variable. A quantitative approach was employed, with data collected through questionnaires distributed to 65 external auditors working at Public Accounting Firms in the Jakarta area. The analytical method used was Moderated Regression Analysis (MRA). The results show that audit experience does not have a significant effect on auditors' ability to detect fraud, while professional skepticism has a positive influence. The direct application of CAATs also does not significantly affect the detection ability; however, CAATs are able to moderate the relationship between professional skepticism and auditors' ability to detect fraud. Conversely, CAATs do not moderate the relationship between audit experience and fraud detection ability. These findings highlight the importance of professional skepticism and technological utilization in enhancing auditors' effectiveness in fraud detection.